Impact in Changing Price Fraction to the Stock Trading Indicators in Indonesia Stock Exchange - Natalia, Natalia; Mulyono, Mulyono; Kurnianingrum, Dian (Binus Business Review, 2016)
The purpose of this study was to determine how the impact of changes the price fraction to the stock trading indicator that is volume, value, and frequency of trading transactions. Data were analyzed using the Mann-Whitney U test. The results show that the volume of stock trading is not affected significantly by the implementation of the tick size, whereas for the value of trade and frequency of trade significantly affected.